2019
DOI: 10.1002/fsn3.1178
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of flavonoids from Sedum aizoon L. against Aeromonas in culture medium and in frozen pork

Abstract: The chemical composition and antimicrobial activity of flavonoids from Sedum aizoon L. against Aeromonas in vitro were investigated, and the effect of flavonoid treatment on the quality of fresh pork during frozen storage for 6 months was also explored. The results showed that kaempferol, quercetin dihydrate, and catechin were the most predominant flavonoids from S. aizoon L. Flavonoids exhibited antibacterial activity to Aeromonas in vitro, which caused membrane damage, disruption of the bacterial surface, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…This also explains why mold and yeast populations were significantly inhibited and contents of mycotoxins were lower during aerobic exposure stages in AA groups, which had significantly higher TF contents in these groups from 60 d fermentation to the whole aerobic exposure as for this study. Furthermore, TF that was negatively with Acetobacter , Enterobacteria , Kazachstania and Pichia , also the same as reports that TF were effective antibacterial against undesirable microorganisms such as Aeromonas , Staphylococcus aureus , Escherichia coli , Fusarium , Aspergillus and some yeasts [ 54 , 55 , 56 , 57 , 58 ]. In conclusion, TF from AA inhibit undesirable microorganisms to improve the quality of fermented feed during the fermentation and aerobic exposure process, and the results also provide further evidence that rarely reported AA can be used as additives in fermented feed.…”
Section: Discussionsupporting
confidence: 80%
“…This also explains why mold and yeast populations were significantly inhibited and contents of mycotoxins were lower during aerobic exposure stages in AA groups, which had significantly higher TF contents in these groups from 60 d fermentation to the whole aerobic exposure as for this study. Furthermore, TF that was negatively with Acetobacter , Enterobacteria , Kazachstania and Pichia , also the same as reports that TF were effective antibacterial against undesirable microorganisms such as Aeromonas , Staphylococcus aureus , Escherichia coli , Fusarium , Aspergillus and some yeasts [ 54 , 55 , 56 , 57 , 58 ]. In conclusion, TF from AA inhibit undesirable microorganisms to improve the quality of fermented feed during the fermentation and aerobic exposure process, and the results also provide further evidence that rarely reported AA can be used as additives in fermented feed.…”
Section: Discussionsupporting
confidence: 80%
“…Meanwhile, this herb could also reduce the risk of chronic and cardiovascular diseases and effectively improve the blood pressure and cholesterol levels in the human body (Xu et al., 2015). The health beneficial properties of Sedum aizoon L. have been confirmed to be attributed primarily to phytochemicals, such as flavonoids, phenolic acids, polysaccharose, and alkaloids according to the previous studies (Lin et al., 2014; Liu et al., 2012; Xu et al., 2019). For instance, it has been reported that Sedum aizoon L. contained high levels of myricetrin, myricetin, quercitrin, quercetin, gallic acid, and kaempferol (Lin et al., 2014; Liu et al., 2012; Xu et al., 2019; Yan, 2013).…”
Section: Introductionmentioning
confidence: 83%
“…The health beneficial properties of Sedum aizoon L. have been confirmed to be attributed primarily to phytochemicals, such as flavonoids, phenolic acids, polysaccharose, and alkaloids according to the previous studies (Lin et al., 2014; Liu et al., 2012; Xu et al., 2019). For instance, it has been reported that Sedum aizoon L. contained high levels of myricetrin, myricetin, quercitrin, quercetin, gallic acid, and kaempferol (Lin et al., 2014; Liu et al., 2012; Xu et al., 2019; Yan, 2013). Sedum aizoon L. has gained much attention as a functional food in the field of food and pharmaceutical sciences due to its functional features (Dong et al., 2020; Liang, Liu, Zhao, & Li, 2009; Liu et al., 2012; Xu et al., 2018; Yan, 2013).…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…It is more active than Dialium corbisieri Staner, aqueous extract on E. coli (ID = 0 and 11 mm), S. aureus (ID = 0 and 10 mm), C. albicans (ID = 0 and 10 mm) [48]. It is likely that the polyphenolic compounds, and particularly flavonoids [59][60][61], would be both responsible for antioxidant and antibacterial activities of leaves and fruits of D. angolense. The antimicrobial activity of flavonoids has previously been demonstrated [62][63][64] and several antimicrobial mechanisms of compounds in these groups have been demonstrated [59].…”
Section: Discussionmentioning
confidence: 99%